“Bitcoin now”: temporal discounting in Bitcoin holders - El Haj, Mohamad; Moustafa, Ahmed A. (Frontiers in Neuroscience, 2023)
Cryptocurrency investment and trading are rapidly growing activities due to the development of applications and platforms that offer fast, continuous, and easy entry into the cryptocurrency world. To understand decision making in cryptocurrency holders, we assessed temporal discounting, that is, whether Bitcoin holders disregard rewards if they are distant in time and overvalue rewards if they are more immediate. Further, we compared performance between short term investors (i.e., day-traders) vs. long-term investors. Using an online survey, we invited 144 Bitcoin holders to answer temporal discounting questionnaires dealing with money (“Which do you prefer, that you get right now 20USD in cash or 100USD in a month?”) and Bitcoin (“Which do you prefer, that you get right now .1 or 1 Bitcoin in a month?”). Analysis demonstrated no significant differences between temporal discounting for money and Bitcoin. However, and critically, higher temporal discounting for both money and Bitcoin was observed in short term investors compared¬ with long term investors. In a similar vein, significant positive correlations were observed between day trading and temporal discounting for both money and Bitcoin. These findings demonstrate how Bitcoin holders with short-term time horizons tend to prioritize immediate rewards over larger but delayed rewards. Future research can assess the neural basis of temporal discounting for cryptocurrencies.